Filiform crystals in meteorites - Semenenko, V.P.; Gorovenko, T.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
The original and literature data on the findings of filiform crystals (FFC) in meteorites are given. It is shown that they have pre-terrestrial and terrestrial origins. Rhabdite crystals in iron meteorites and pallasites, taenite ones in ataxites, and graphite ones in carbonaceous xenoliths of chondrites are the most common among the pre-terrestrial FFC. It is assumed that their formation is a result of solid phase transformations during the slow cooling of meteorite parent bodies. Unlike them, the olivine and Ca-pyroxene FFC within a fine-grained matter of chondrites and Fe,Ni-metal FFC in pallasites are rare. The morphological characteristics of the meteoritic FFC are similar to those of the artificially grown ones, although they differ by a narrower variety of crystallographic forms and the priority of formation conditions.